2022
DOI: 10.3389/fgene.2022.827274
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Epigenetic Mechanisms in the Development of Retinitis Pigmentosa and Related Photoreceptor Dystrophies

Abstract: Retinitis pigmentosa and related photoreceptor dystrophies (RPRPD) are rare retinal diseases caused by hereditary gene mutations resulting in photoreceptor death, followed by vision loss. While numerous genes involved in these diseases have been identified, many cases have still not been associated with any gene, indicating that new mechanisms may be involved in the pathogenesis of these photoreceptor dystrophies. Many genes associated with RPRPD regulate photoreceptor specification and maturation in the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…DNA methylation and demethylation are important epigenetic mechanisms in the pathogenesis of retinal diseases. Based on this, Dvoriantchikova et al (2022) proposed an epigenetic RP model by suppressing demethylation of genes which are essential for transition from RPC-to-photoreceptor without any mutations. DNA methyltransferase and demethylase have been recognized to be involved in the repair of C/T mismatch caused by deamination of methylated cytosine in BER pathway, and PARP1 could regulate the activity of target protein through recruitment of demethylases ( Maiti and Drohat, 2011 ; Weber et al, 2016 ; Sutcu et al, 2019 ; Jiang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation and demethylation are important epigenetic mechanisms in the pathogenesis of retinal diseases. Based on this, Dvoriantchikova et al (2022) proposed an epigenetic RP model by suppressing demethylation of genes which are essential for transition from RPC-to-photoreceptor without any mutations. DNA methyltransferase and demethylase have been recognized to be involved in the repair of C/T mismatch caused by deamination of methylated cytosine in BER pathway, and PARP1 could regulate the activity of target protein through recruitment of demethylases ( Maiti and Drohat, 2011 ; Weber et al, 2016 ; Sutcu et al, 2019 ; Jiang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The need to understand mutations in the epigenetic landscape is crucial to moving forward with additional therapies and targets for human patients. While there are not many studies examining the effects of epigenetic mutations in IRDs [ 53 ], many epigenetic marks play a role in the expression and variability of retinal genes involved in phototransduction and development [ 54 , 55 ]. It is important to take into consideration the potential effects that DNA or histone methylation have on the pathogenesis of IRDs over time.…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging evidence also suggests that epigenetic modifications may contribute to the pathogenesis of these disorders. Specifically, unsuccessful demethylation of regulatory sequences (e.g., promoters, enhancers) during the transition from retinal progenitor cells to photoreceptors may reduce or eliminate the activity of genes required for photoreceptor development, maturation, and function, potentially leading to RPRPD even in the absence of genetic mutations (Dvoriantchikova et al, 2022). While further study is needed to confirm the extent of epigenetic contributions to RP and RPRPD, these findings suggest a potential new avenue for therapeutic intervention.…”
Section: Regulation Of Photoreceptor Death and Degeneration By Methyl...mentioning
confidence: 96%
“…In contrast, the role of DNA methylation and DNA demethylation pathways in the differentiation of RPCs to non-photoreceptor retinal phenotypes may be less critical (Dvoriantchikova et al, 2019). Another study confirmed these findings, indicating that gene promoters essential for rod and cone photoreceptor fate specification and maturation, such as Crx, Nrl, Nr2e3, Pde6a, Pde6g, Pde6c, Pde6h, Gnat1, Rho, Ush2a, Prph2, etc., are hypermethylated in RPCs and demethylated during the transition from RPCs to photoreceptors (Dvoriantchikova et al, 2022). Additionally, the Wnt signaling pathway can inhibit cellular differentiation in the retina (Kubo et al, 2005).…”
Section: Regulation Of Photoreceptor Differentiation By Dna Methylationmentioning
confidence: 99%